Non-Communicable Diseases in Fragile, Conflict, and Violence Situations : Five Key Questions to be Answered - Carrette, Sheila; Dong, Di; Hasumi, Takahiro (World Bank, Washington, DC, 2018)
The global burden of disease has shifted from that of communicable to non-communicable diseases (NCD) in many countries. This note highlights the need for investment, as well as best practices in designing, implementing and evaluating a project that includes an NCD focus or component within an fragile, conflict, and violence (FCV) setting.